Brands with a conscience how to build a successful and responsible brand - Horlings, Sandra; Ind, Nicholas (Kogan Page, 2016)
Providing a set of foundational attributes to help guide a strategy for responsible growth, this inspiring book includes a range of practical tools that bring these concepts together to guide managers in building a brand strategy based on real world experience.